Premature deaths, accidental bequests and fairness - Marc Fleurbaey; Marie-Louise Leroux; Pierre Pestieau; Gregory Ponthiere; Stephane Zuber (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
While little agreement exists regarding the taxation of bequests in general, there is a widely held view that accidental bequests should be subject to a confiscatory tax. We propose to reexamine the optimal taxation of accidental bequests in an economy where individuals care about what they leave to their ospring in case of premature death. We show that, whereas the conventional 100 % tax view holds under the standard utilitarian social welfare criterion, it does not hold under the ex post egalitarian criterion, which assigns a strong weight to the welfare of unlucky short-lived individuals. From an egalitarian perspective, it is optimal not to tax, but to subsidize accidental bequests. We examine the robustness of those results in a dynamic OLG model of wealth accumulation, and show that, whereas the sign of the optimal tax on accidental bequests depends on the form of the joy of giving motive, it remains true that the 100 % tax view does not hold under the ex post egalitarian criterion.
Keywords: 330